2022
DOI: 10.1155/2022/8523763
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Big Data Clustering and Visual Communication in Business Website Interface Design

Abstract: The interface design of commercial websites is used in this paper to demonstrate the application of big data clustering and visual communication technologies. This paper presents the new requirements of user integration, emotion, and personalization by analyzing the broad influence of big data clustering technology and visual communication on the design concept and design method of commercial website interface design. Then, focusing on the information of visual graphic elements in web interface design and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Web design includes many visual elements, such as the text content, image content, color matching, and panel design of the web page 3 . The role of visual elements in web design is mainly to beautify web pages 4 . It can incorporate different content into web design.…”
Section: Introductionmentioning
confidence: 99%
“…Web design includes many visual elements, such as the text content, image content, color matching, and panel design of the web page 3 . The role of visual elements in web design is mainly to beautify web pages 4 . It can incorporate different content into web design.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development and application of big data technology, more data are collected and stored, and the information becomes more rich and complex [1][2]. These data contain customers, markets, products, and brands, which can provide valuable references and decision-making bases for art design and other fields [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%